Hearing Screening Test Mobile Games Application for Kids - Bhopal, Pevinder Kaur Rajinder Singh; Senan, Norhalina (Applied Information Technology And Computer Science, 2022)
In literature, around 34 million children suffer from hearing impairment, and it does not happen overnight. As a result, parents should keep an auditory check on their children at all times. Unfortunately, the existing applications available are not suitable for children due to their complexity level. This paper outlines the creation of an Android-based application KidzLing, which implements the Ling Six Sound Check approach to conduct the screening test. KidzLing is a 2D mobile application that performs screening tests using the gamification approach for children aged three to six years. The ADDIE model, which consists of five phases: analysis, design, development, implementation, and evaluation, used to assist the project development. The software opted for the development process is Unity 2D, Visual Studio for C# scripting, and Adobe Illustrator for asset creation. Firebase Realtime cloud database is selected to store the user's data. The findings of beta testing show KidzLing is completely functioning as expected. In addition, the application's usability score on the System Usability Scale (SUS) is 89%, which is within the acceptable range.